DEVELOPING ISLAMIC READING MATERIAL OF PROCEDURE TEXT BASED ON SCIENTIFIC APPROACH FOR GRADE ELEVEN AT SMA NURUL ISLAM INDONESIA MEDAN - Indah Sari Devi; Rahmad Husein (Universitas Negeri Medan, 2021)
This study aims to develop English Reading Material for Grade Eleven of Islamic Students at SMA Nurul Islam Indonesia Medan. This study was conducted by using Research and Development (R & D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subject of this study were students of class XI IPA consisting of 30 students and one of the English teachers. The instrumentation for collecting the data were questionnaire and interview. After Analyzing the data, the researcher got the students’ needs. The data were gathered by administrating interview to English teacher and distributing the questionnaire to 30 students to get the students’ needs. The interview and questionnaire result prove that the Islamic 1 students of XI IPA need English reading materials which contain Islamic content. Thus, developing English reading materials were procedure text. Then the procedure texts related to their background of knowledge. The products have been validated by two experts; English lecturer and English teacher. The average scores are 4.6 or 92% from English lecturer and 4.4 or 89% from English teacher. It means the developing materials are categorize as relevant or appropriate for grade eleven of Islamic students.Keywords: Research and Development (R & D), reading materials, Islamic students